تأثير قرار التوزيع على سياسة الاستثمار في المؤسسة الاقتصادية - دراسة ميدانية بمؤسسة مطاحن بلغيث الكبرى بولاية سوق أهراس - أحلام صيد; مفيدة بن سلامة (My University, 2021)
This study aims to know the extent of the impact of the distribution decision on the investment policy in the company , because the distribution decision is crucial financial decisions in the entreprise ; as well as the investment decision. In order to examine this relationship, the study was carried out in the « Balghith Mills Corporation ». using its financial statements represented in the results accounts table and the financial budget by analysing financial ratios over a period of three years (2018-2019-2020). This study concluded that there is a significant impact on the distribution decision on the investment policy, which shows the importance of the taking decision about distribution or detention, as well as the study recommended the importance of institutions reliance on a specific policy in the distribution of profits. ...................................................... تهدف هذه الدراسة الى معرفة مدى تأثير قرار التوزيع على سياسة الاستثمار في المؤسسة الاقتصادية ذلك لأن قرار توزيع الأرباح يعتبر من أهم القرارات المالية في المؤسسات وكذا قرار الاستثمار، ومن أجل معرفة هذه العلاقة تمت هذه الدراسة في مؤسسة »مطاحن بلغيث الكبرى « وذلك بالاعتماد على قوائمها المالية المتمثلة في كل من جدول حسابات النتائج والميزانية المالية وتحليلها باستخدام النسب المالية وهذا مدى ثلاث سنوات ) 2018-2019- وصلت هذه الدراسة الى وجود أثر كبير في قرار توزيع الأرباح على سياسة الاستثمار، مما يههر هنا أميية اخااذ المؤسسة لقرار التوزيع أو الاحتجاز، كذلك أوصت الدراسة بأميية اعتماد المؤسسات على سياسة محددة في توزيع الأرباح.